PENGARUH PENGALAMAN WISATAWAN TERHADAP CITRA DESTINASI PARIWISATA Kasus : Jl. Malioboro dan Jl. Ahmad Yani, Yogyakarta - , ZULFIANA SETYANINGSIH, Dr. Ir. Djoko Wijono, M.Arch. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Malioboro, known as icon of Yogyakarta tourism, is one of the favorite destinations for both domestic and foreign tourists. As the special destination, this area offers special interest tourism such as shopping, culinary, culture and nostalgia. Beside that, its supported by an adequate facilities and good accessibility. However, on the other hand many tourists complain of discomfort in this area, such as about cleanliness, parking lot, pedestrian, traffic congestion, safety, and price. In the study of theories, experience is one of the factors that influence the image of tourism destinations, so that more and more good impression of experience subsequently produce a positive image. Ideally, Malioboro should be able to present a memorable experience for tourists, even zero complain, so further that will supported the positive image of Malioboro. Based on the potential and the weakness it has, it needs to be identified that the tourist experiences influences the image of Malioboro, which would then be used to find a strategy for development of Malioboro. The analysis conducted of this study were the verification analysis method by hypothesis testing and descriptive analysis method for supporting hypothesis test. The hypothesis of this study is that the tourist experience influence the image of Malioboro. The statistical method used to test this hypotheses is Spearman Rank correlation. Analyses were performed by using SPSS-20 for Windows. The results showed unsubstantiated hypothesis. This means that the conditions on the field has contradiction with the study of theories, so it can be said, "it is not necessary the good tourist experience would influences the image to be good, or conversely, bad experience influences the image to be bad". In the case of Jl. Malioboro dan Jl. Ahmad Yani, there are factors beyond the destination firmly established imaging Malioboro. These factors led to the media because it is being able to provide more access to the public knowledge of developments in Malioboro.. This is demonstrated by the many media that highlight Malioboro by comparing the historical romantism while ago with the development of the current. Average media criticize and discuss that there has been quality degradation of the atmosphere or the essence of Malioboro caused by commercialization, density and traffic chaos.. This is influence to the background information of the tourists. Therefore it is very important using of advances in information technology through a variety of media to promote Malioboro and increase involvements of academics community in imaging Malioboro as a counterweight, so it would be neutral, proportional and not carrying the interest of any party opinion.